Spatial Distribution Pattern of Village Development Index in Karawang Regency Using Spatial Autocorrelation Approach - Murtadho, Alfin; Pravitasari, Andrea Emma; Munibah, Khursatul; Rustiadi, Ernan (Universitas Diponegoro, Indonesia, 2020)
Jabodetabek and Greater Bandung Metropolitan areas experiencing the phenomenon of urban expansion which has caused both metropolitan areas to be more connected and become a mega-urban area by a corridor through a conurbation process. Karawang regency is part of the region in the Jakarta-Bandung corridor. The increasing number of population in the region will encourage the addition of number and types of public facilities. The objectives of this study were to analyze the regional development and spatial distribution pattern of the Village Development Index/ Indeks Perkembangan Desa (IPD) in Karawang regency. Regional development was analyzed using scalogram analysis, while spatial distribution pattern of the IPD was analyzed using Global and Local Moran Index. Regional development analysis shows the distribution of the IPD in 2014 has increased from 2003. Analysis of spatial distribution pattern of IPD values from 2003 and 2014 shows the clustered distribution patterns in some sub-districts.